METHODOLOGY FOR PREPARING FUTURE PHYSICS TEACHERS FOR TEACHING A MECHANICS COURSE IN DIGITALIZATION CONDITIONS - Alazharova С.; Issayeva Г.; Yerzhenbek Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The development of modern technologies contributes to the emergence of new teaching methods. The modern world is difficult to imagine without the use of technology. The growth of digitalization simplifies the learning process, but requires the creation of a new methodology. Moreover, this technique implies a high level of computer literacy among future teachers. The article proposes methods for teaching a mechanics course using computer technology. Using ICT (information and communication technologies) you can demonstrate experiments, show bright, interesting presentations, and solve problems. The author of the article offers several applications that help solve problems more clearly and quickly. The use of modern teaching methods greatly simplifies the process of explaining topics and solving problems, but requires a fairly high level of PC proficiency. Accordingly, future teachers need to acquire the necessary skills while still at the university. To teach this course using modern technologies, you must be able to use the applications in practice, as well as have basic programming skills. This is necessary so that students can clearly demonstrate the simulated processes and show how to perform calculations using the Mathcad package and other important application programs. The advantages of learning using ICT also lie in the fact that students, at the end of the course, will not only master the program material, but will also improve their PC skills.